Alcohol Dehydrogenase 1B Suppresses β-Amyloid-Induced Neuron Apoptosis - Wang, Yaqi; Zhang, Yi; Zhang, Xiaomin; Yang, Tingting; Liu, Chengeng; Wang, Peichang (Frontiers in Aging Neuroscience, 2019)
β-amyloid (Aβ) deposition, neurofibrillary tangles induced by phosphorylation of tau protein, and neuronal apoptosis are pathological hallmarks of Alzheimer’s disease (AD). The dementia rate in alcoholic abusers were found to be higher than in control people. The present study explored the potential roles of alcohol dehydrogenase 1B (ADH1B) in AD pathology by determining the ADH1B levels in AD patient sera, in the hippocampus of APP/PS-1 AD model mice, and in an AD model cell line treated with Aβ1-42. The results show that ADH1B levels decreased significantly both in the serum of AD patients and in the hippocampus of APP/PS-1 AD model mice. In addition, the apoptotic rate was reduced and viability was significantly increased in AD model cells transfected with ADH1B overexpression vector. The levels of the p75 neurotrophin receptor (p75NTR), an Aβ1-42 receptor, were down-regulated in the ADH1B overexpressing AD model cell and up-regulated in cells transfected with the shRNA vector of ADH1B. Protein levels of cleaved caspase-3 and Bax decreased significantly, whereas Bcl-2 levels increased in cells overexpressing ADH1B. The opposite trend was observed for cleaved caspase-3, Bax, and Bcl-2 levels in cells transfected with the shRNA vector of ADH1B. The levels of reactive oxygen species (ROS) were found to be reduced in ADH1B overexpressing cells and increased when cells were transfected with the shRNA vector of ADH1B. These results indicate that ADH1B might be important in the prevention of AD, especially for abusers of alcohol, and a potential new target of AD treatment.